Implementasi Sistem Aplikasi Absensi Online Berbasis Vue.Js Pada PT. PPILN Dengan Metode RAD - Suprapto; Ario Fajar (Prosiding Sains dan Teknologi, 2024)
This research aims to design and implement a Vue.js-based online attendance application for PT. PPILN. The main objective is to enhance the efficiency of field technicians in recording their attendance. The application replaces the traditional method of using pen and paper, which is time-consuming and requires administrative resources. The research includes the analysis of requirements and the design of a responsive and user-friendly online attendance application. The implementation results demonstrate improved efficiency in attendance recording for field technicians, allowing them to record their attendance directly in the field. The application also minimizes the risk of errors and enables real-time tracking of the technicians' whereabouts by the management of PT. PPILN. The RAD research method will be utilized in this study. The data used will be internal data from PT. PPILN concerning the technical staff and the attendance process.